Agencja Nieruchomości Rolnych - restrukturyzacja czy likwidacja? - Czechowski, Paweł (Wydawnictwo Naukowe UAM, 2008)
A question is posed whether the Agricultural Property Agency should be liquidated or restructured. This issue is discussed on the basis of the existing legal regulations and experience, recommending, in conclusion, the latter option. Consequently, three restructuring solutions are offered. The first one, modelled on the French solution SAFER, consists in the transformation of the Agency into an institution whose task would be to shape the turnover and structure of agricultural property. This institution, acting as a group of public companies in a decentralised system, and having a central, or federal structure, would implement the noncommercial mission of the public interest, creating agricultural holdings of desired sizes, or propagating settlements in desired areas. The second model provides for the transformation of the Agency into an entity that would manage the agricultural property of the State Treasury. Such a structure would resemble the Spanish model 1RYDA, and would provide for a centralised structure appointed within the structures of the Ministry of Agriculture and Rural Development, and the regional public entities supervised by ministerial territorial agencies. The third model that is worth considering is gradual transformation of the current Agency and resulting from it gradual elimination of the fiduciary role of the State Treasury. If that model is adopted, this process should have been completed before state agricultural property has been fully privatised. At that time the Agricultural Property Agency should be transformed in a state entity with a legal status.

L’Autore, in base all’analisi delle norme giuridiche e delle esperienze finora acquisite, cerca, in primo luogo, di rispondere alia domanda se l’Agnezia dei Fondi Agricoli dovrebbe essere liquidata o piuttosto ristrutturata. Una volta constatato che é piü opportuna la seconda soluzione, analizza tre possibili opzioni in mérito. La prima presuppone, sulla falsariga delle esperienze francesi sul SAFER, la trasformazione dell’Agenzia in un ente di indirizzo in mérito alia circolazion della circolazione e delle strutture fondiarie. Tale ente, operante come un insieme di societá pubbliche nel sistema decentralizzato e avente la struttura federale, potrebbe realizzare finalitá pubbliche non commerciali, consistenti nella creazione di aziende agricole di dimensioni adeguate nonché nel favorire Pinsediamento degli agricoltori. La seconda soluzione presuppone la trasformazione dell’Agenzia in un soggetto che svolge fiinzioni di gestione della proprietá agrícola dello Stato. Tale soggetto dovrebbe essere simile al modello spagnolo di 1RYDA, che richiede Pesistenza di una struttura decentralizzata istituita nell’ambito della struttura del Ministero dell’Agricoltura e dello Sviluppo Rurale nonché nell’ambito delle imprese pubbliche regionali controllate dalle agende ministeriali nel territorio. La terza proposta che occorre considerare consiste nella trasformazione del modello attuale ed implica la gradúale abolizione del sistema fiduciario del Tesoro dello Stato finora operante. Tale operazione dovrebbe essere portata a termine prima della fine del processo di privatizzazione dei fondi agricoli statali. In base a questi presupposti PAgenzia dovrebbe essere trasformata in un ente organizzativo statale dotato di personalitá giuridica.
Agricultural property agency - liquidation or restructuring?
Agenzia dei fondi agricoli - abolizione o ristrutturizzazione?